2017
DOI: 10.1016/j.immuni.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Regulation of Group 3 Innate Lymphoid Cells and the Immunoresolvent PCTR1 Controls Infection Resolution

Abstract: Summary Uncovering mechanisms that control immune responses in the resolution of bacterial infections is critical for the development of new therapeutic strategies that resolve infectious-inflammation without unwanted side effects. Herein, we found that disruption of the vagal system in mice delayed resolution of Escherichia coli infection. Dissection of the right vagus decreased peritoneal Group 3 innate lymphoid cell (ILC3) numbers and altered peritoneal macrophage responses. Vagotomy resulted in an inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 33 publications
4
161
2
Order By: Relevance
“…Experiments utilizing vagotomy in a mouse model of zymosan-induced peritonitis indicated that vagus nerve cholinergic signaling promotes resolution processes in the lungs and abdominal tissues, mediated by netrin-1, an axonal guidance molecule and newly identified proresolving molecule (109). Vagus nerve cholinergic signaling was also implicated in enhancing inflammation resolution in response to bacterial infection (110). This neural control affects peritoneal group 3 innate lymphoid cells and the release of the protective resolvent molecule PCTR1 (110).…”
Section: Functional Neuroanatomy For Communication With the Immune Symentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments utilizing vagotomy in a mouse model of zymosan-induced peritonitis indicated that vagus nerve cholinergic signaling promotes resolution processes in the lungs and abdominal tissues, mediated by netrin-1, an axonal guidance molecule and newly identified proresolving molecule (109). Vagus nerve cholinergic signaling was also implicated in enhancing inflammation resolution in response to bacterial infection (110). This neural control affects peritoneal group 3 innate lymphoid cells and the release of the protective resolvent molecule PCTR1 (110).…”
Section: Functional Neuroanatomy For Communication With the Immune Symentioning
confidence: 99%
“…Vagus nerve cholinergic signaling was also implicated in enhancing inflammation resolution in response to bacterial infection (110). This neural control affects peritoneal group 3 innate lymphoid cells and the release of the protective resolvent molecule PCTR1 (110). These findings highlighting a role of the efferent vagus nerve in inflammation resolution in addition to its anti-inflammatory control suggest that the vagus nerve may function as an integrator of inflammatory stages.…”
Section: Functional Neuroanatomy For Communication With the Immune Symentioning
confidence: 99%
“…Dysregulation in pro-resolving mediator signaling is associated with unresolved chronic inflammation, which drives pathology in a myriad of diseases (Serhan, 2014; Nathan and Ding, 2010). Recent findings indicate that inflammation resolution is regulated by neural signaling along the vagus nerve (Mirakaj et al, 2014; Dalli et al, 2017). Experiments with vagotomy (unilateral cervical) in a mouse model of zymosaninduced peritonitis revealed that vagus nerve signals control the lung and abdominal tissue expression of netrin-1, an axonal guidance molecule, rediscovered as an innate immune system pro-resolving mediator (Mirakaj et al, 2014).…”
Section: Efferent Neurocircuitry In the Regulation Of Immunitymentioning
confidence: 99%
“…Continued investigation along these lines permitted elucidation of three separate pathways, coined MCTRs, PCTRs and RCTRs. The stereochemistry of MCTR1, MCTR2 and MCTR3 and PCTR1 (Dalli et al, 2016a; Ramon et al, 2016) are established (Figure 2), and they are produced in mouse lymphoid tissues and in infectious inflammatory exudates as well as in specific human tissues (Dalli et al, 2017a). …”
Section: Resolution Mediators and Tissue Regenerationmentioning
confidence: 99%